2016
DOI: 10.3389/fpls.2016.00987
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Traits Associated with Wheat Yield Potential and Performance under Water-Stress in a Mediterranean Environment

Abstract: Different physiological traits have been proposed as key traits associated with yield potential as well as performance under water stress. The aim of this paper is to examine the genotypic variability of leaf chlorophyll, stem water-soluble carbohydrate content and carbon isotope discrimination (Δ13C), and their relationship with grain yield (GY) and other agronomical traits, under contrasting water conditions in a Mediterranean environment. The study was performed on a large collection of 384 wheat genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 60 publications
8
72
0
1
Order By: Relevance
“…3). These differences in the relationship between D 13 C and grain yield depending on the tissue analyzed and the water environment have been observed before in common bean and wheat (Zhou et al, 2014;del Pozo et al, 2016;Polania et al, 2016b). Given that shoot samples were collected earlier in the season in comparison with grain samples and with respect to the TDS imposition, the closer relationship of grain D 13 C to grain yield was not surprising and was consistent with the D 13 C signature integrating the plant response to environmental conditions over different time periods (Farquhar et al, 1989;Condon et al, 2004).…”
Section: Relationships Between Yield and Physiological And Agronomic supporting
confidence: 64%
See 1 more Smart Citation
“…3). These differences in the relationship between D 13 C and grain yield depending on the tissue analyzed and the water environment have been observed before in common bean and wheat (Zhou et al, 2014;del Pozo et al, 2016;Polania et al, 2016b). Given that shoot samples were collected earlier in the season in comparison with grain samples and with respect to the TDS imposition, the closer relationship of grain D 13 C to grain yield was not surprising and was consistent with the D 13 C signature integrating the plant response to environmental conditions over different time periods (Farquhar et al, 1989;Condon et al, 2004).…”
Section: Relationships Between Yield and Physiological And Agronomic supporting
confidence: 64%
“…Like common bean, observations in other species also indicate complex relationships of D 13 C and seed yield (Brito et al, 2014;Vadez and Ratnakumar, 2016). For instance, in wheat (Triticum aestivum L.), D 13 C signature and yield were positively correlated under moderate drought conditions Fischer et al, 1998;Merah et al, 2001), but negatively correlated under severe drought conditions (del Pozo et al, 2016). Although relationships with yield can be inconsistent, D 13 C signatures generally closely relate to g s and WUE and, as such, can provide valuable information about physiological mechanisms associated with drought resistance.…”
mentioning
confidence: 99%
“…These different yield responses to irrigation for the three spring wheat cultivars in the first season were probably related to little rainfall (especially in spring) coupled with poor distribution. Indeed, Loss and Siddique [52], Passioura [89] and Del Pozo et al [90] showed that the best yield was produced when SI matches plant growth and water demand, while Rasmussen et al reported that yield was commonly greater if rainfall was partially distributed during the spring months, predominantly in May and June. To avoid a possible decline in yield with small rainfall amounts in spring months, SI supply during this stage of the crop growth was found to regulate and stabilize yield under the Mediterranean conditions of northern Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…Water stress has been considered a cause of variable impacts on plant growth (Bernal et al, 2015;Chaves, Maroco, & Pereira, 2003;Llorens, Penuelas, Estiarte, & Bruna, 2004;del Pozo et al, 2016), and the responses of plant species to water stress may vary among species, as mediated by their functional traits (Körner, 2003;Llorens et al, 2004;Smirnoff, 1993;Violle et al, 2007). Considering a plant species as having a set of morphological and physiological traits which have impacts on the performance of plants (Violle et al, 2007) greatly increases our possibility for examining the differences among plant species in response to environmental variability.…”
Section: Introductionmentioning
confidence: 99%